Cell lineage-specific transcriptome analysis for interpreting cell fate specification of proembryos - Zhou, Xuemei (Nat Commun, 2020)
In Arabidopsis, a zygote undergoes asymmetrical cell division that establishes the first two distinct cell types of early proembryos, apical and basal cells. However, the genome-wide transcriptional activities that guide divergence of apical and basal cell development remain unknown. Here, we present a comprehensive transcriptome analysis of apical and basal cell lineages, uncovering distinct molecular pathways during cell lineage specification. Selective deletion of inherited transcripts and specific de novo transcription contribute to the establishment of cell lineage-specific pathways for cell fate specification. Embryo-related pathways have been specifically activated in apical cell lineage since 1-cell embryo stage, but quick transcriptome remodeling toward suspensor-specific pathways are found in basal cell lineage. Furthermore, long noncoding RNAs and alternative splicing isoforms may be involved in cell lineage specification. This work also provides a valuable lineage-specific transcriptome resource to elucidate the molecular pathways for divergence of apical and basal cell lineages at genome-wide scale.